PENINGKATAN NILAI PENDAPATAN PERAJIN TUSUK SATE DENGAN DIVERSIFIKASI PRODUK - Talha Dangkua; Suleman Dangkua; Rubiyanto Maku; Riklan Kango; Eska Zuhriana Adam (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2023)
Timuato Village is known as the place of production of bamboo skewers. It has been passed down from ancestors to nowadays generation. However, the quality and quantity of the bamboo skewers are still low. There are some problems which the craftswomen face, firstly, the low variety of the product, secondly, the packaging of the product is not attractive, and thirdly, the product marketing strategy is not very good. This program aims to increase the income of skewer craftsmen by increasing the variety of the products. This program is to train and mentor the skewer craftswomen to improve the variety, quantity, and quality of the product. The first training stage is to produce better quality and quantity skewer products. They were also trained to increase the variety of bamboo products with various shapes, models, and functions. Another training is Product packaging training to make product packaging more attractive. Lastly, digital marketing training was also held to develop a marketing strategy to reach customers outside Gorontalo. Most of the craftswomen have Junior high school backgrounds. Throughout this program, they are given the opportunity to learn, be supported by production tools, and to strengthen their motivation.